Effective Project Leadership Styles for Hybrid Teams in the Australian Banking Industry - Shrestha, Brinda (Digital Repository of Theses, 2024)
The Australian banking industry has seen a significant shift towards hybrid work models. This has necessitated effective project leadership to navigate the challenges of managing both remote and face-to-face teams. Although there is a growing focus on project leadership in a hybrid environment, literature on this domain is scarce. There is a limited understanding of the relationship between a Project Manager’s leadership style, Leader-Member Exchange (LMX), and project performance in a hybrid environment. A multi-dimensional Project Leadership Framework, consisting of Ethical, Authentic, Transactional, and Transformational leadership styles, was conceptualized based on the extensive literature review. The Project Leadership Research Model was then developed to validate the multi-dimensionality and effectiveness of a Project Manager’s leadership styles. The study focused on the hybrid project teams in the Australian banking industry and identified the Project Manager’s key leadership styles that can lead to project success. It also examined whether LMX mediates the relationship between Project Manager’s leadership styles and project success. A positivist philosophy with a deduction approach was used to collect data through an online Google Forms survey for quantitative analysis using SPSS Version 29.0. Descriptive and inferential statistics like means, correlation, factor analysis, ANOVA, and regression analyses were used to statistically analyze the data gathered from a valid sample of 82 respondents. The study validated the overlap of leadership styles and the multi-dimensionality of project leadership. It highlighted the critical role of effective leadership styles, particularly Ethical, Authentic, and Transformational, in enhancing project performance within the Australian banking industry. While positively impacting project performance, Transactional Leadership exhibited a weaker influence than other styles. Furthermore, the study revealed that LMX partially mediated the relationship between leadership styles and project performance, underscoring the importance of strong, trust-based relationships between Project Managers and project team members. These findings contribute to the existing body of knowledge on leadership theories and offer practical recommendations for leadership development and improving leadership effectiveness to navigate the complexities of hybrid project teams in the banking industry. Key Words: Hybrid project teams; project management; project manager, authentic leadership; ethical leadership; transactional leadership; transformational leadership; leader-member exchange; project success; project performance; multi-dimensional leadership approach; hybrid work model.